Avaliação química e sensorial de café Catuaí amarelo fermentado pelo processamento por via seca com inoculação de leveduras - Bressani, Ana Paula Pereira (2017)
Coffee is a popular beverage consumed all over the world and its quality is directly related to taste and aroma. The objective of this study was to evaluate the action of selected yeasts in different inoculation methods (directly inoculated cherry coffee by dry fermented in suspended terrace for drying in the sun (D) and in buckets for 16 hours before being taken to the suspended terrace (B)) for drying in the sun. Saccharomyces cerevisiae CCMA 0543, Candida parapsilosis CCMA 0544 and Torulospora delbrueckii CCMA 0684 were inoculated separately and the control without inoculation. The centesimal composition was evaluated in the coffee fruit. Samples were collected for the analysis of qPCR (persistence of the inoculum) and for the chemical analysis by HPLC (caffeine, chlorogenic acids, trigonelline and sugars) and GC-MS (volatile compounds). Sensory analysis was performed in roasted coffee using cup proof in according to Specialty Coffee Association of America (SCAA). All treatments with directly inoculated yeasts showed higher concentrations of citric and malic acids when compared to the bucket method. Concontration of caffeine, chlorogenic acids and trigonelline varied between methods of inoculation. In all, two hundred and seventeen volatile compounds were identified. All treatments origitaned special coffees, and the Saccharomyces cerevisiae 0543 B treatment obtained the highest score in the cup test, with notes of banana and cashew. Direct inoculated Candida parapsilosis CCMA 0544 was better than the same treatment inoculated in bucket and Torulospora delbruekii CCMA 0684 showed good results for both methods used.